Understanding Thai consumer attitudes and expectations of ginseng food products - Peerarat Doungtip (2020)
© 2019 Wiley Periodicals, Inc. Ginseng is now increasingly popular in Thailand because of its multifunctional health properties. However, the recognition and acceptance of ginseng food products in Thailand have been limited. The objectives of this research were to investigate consumer attitudes toward ginseng products and to obtain useful information to develop ginseng food products that meet the expectations of Thai consumers. Consumer surveys and focus group interviews were conducted. The 430 respondents participated in the consumer surveys. Six focus group interviews (n = 51) were also conducted. Results showed that most Thai consumers know ginseng. Ginseng is representative of a healthy image. Consumers wanted new products, such as beverages, and this product should be easily absorbed or digested. For focus group interviews, older participants (more than 40 years old) had positive impressions toward ginseng food products in contrast to young participants. Participants were concerned about convenience, price, and taste and aroma of new ginseng products. Practical applications: The study of Thai consumer attitudes and expectations of Korean ginseng products posed an interesting challenge and could provide information for promoting Korean ginseng in Thailand. The results of this research can be used for idea generation and further development studies on ginseng products. Advertisement and education may also increase consumption of ginseng food products among Thai consumers.